The Influence of the STEM Approach on High School Students' Mathematical Problem Solving Ability in Trigonometry - Zulfa Lailaturrosidah; Agus Maman Abadi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the effectiveness of the STEM approach and the scientific approach in learning Trigonometry in terms of students’ mathematical problem-solving ability and self-efficacy. The research employed a quasi-experimental method with a nonequivalent comparison group design. The study population consisted of all Grade X MIPA students at MA Al-Ma’had An-Nur in the 2023/2024 academic year, with the sample taken from classes X MIPA 1 and X MIPA 2. Data collection instruments included pre-test and post-test assessments of mathematical problem-solving ability and a student self-efficacy questionnaire. Effectiveness criteria were based on post-test averages exceeding 75 for problem-solving ability and self-efficacy scores above 72, as well as improvements from pre-test results. Data were analyzed using the t-test at a 5% significance level to determine learning effectiveness in both groups. Differences in students’ initial conditions and treatment effects were examined using Hotelling’s T² and the N-Gain score test. An independent-sample t-test of N-Gain was used to compare the superiority between the two approaches. The results indicated that both the STEM and scientific approaches were effective in improving students’ mathematical problem-solving ability and self-efficacy. The STEM approach significantly influenced both variables and was superior in enhancing problem-solving ability, although not superior in improving students’ self-efficacy.